2011
DOI: 10.1093/ecam/nep159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Adjustment on Drug Interactions through Intestinal CYP3A Activity in Rat: Impacts of Kampo Medicines Repeat Administered

Abstract: To provide the information that is necessary for making the proper use of kampo medicines, we have proposed the adequate methodology focused on the following issues: (i) kampo medicines emphasize the effects produced by the combination of herbal drugs rather than the individual effect of any single herb and (ii) Intestinal CYP3A has become a key factor for the bioavailability of orally administrated drugs. In the present study, we investigated both the in vivo and in vitro effects of Saireito and Hochuekkito (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We examined changes in intracellular drug concentration using LS180 cells, which are a suitable intestinal epithelial cell model to analyze interactions between drugs and epithelial cells ( Gupta et al, 2008 ; Lau et al, 2013 ), although in vivo studies are needed to confirm our findings. A previous study demonstrated that hochuekki-to containing CP increased CYP3A4 expression in the intestine and decreased the area under the curve for the CYP3A4 substrate nifedipine ( Kinoshita et al, 2011 ). This indicated that that induction of P-gp and CYP3A4 protein via upregulation of PXR in intestinal epithelial cells may occur in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined changes in intracellular drug concentration using LS180 cells, which are a suitable intestinal epithelial cell model to analyze interactions between drugs and epithelial cells ( Gupta et al, 2008 ; Lau et al, 2013 ), although in vivo studies are needed to confirm our findings. A previous study demonstrated that hochuekki-to containing CP increased CYP3A4 expression in the intestine and decreased the area under the curve for the CYP3A4 substrate nifedipine ( Kinoshita et al, 2011 ). This indicated that that induction of P-gp and CYP3A4 protein via upregulation of PXR in intestinal epithelial cells may occur in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Immature orange [ Aurantii fructus immaturus (IO)] and citrus unshiu peel [ Citri unshiu pericarpium (CP)] are common ingredients of kampo that are reported to have anti-hypercholesterolemic or orexigenic effects ( Yoshie et al, 2004 ; Hayakawa et al, 2014 ). However, a previous study reported that kampo containing IO or CP decreased the blood concentration of concomitantly administered CYP3A4 substrates via upregulation of CYP3A4 although the mechanism was unclear ( Kinoshita et al, 2011 ). IO and CP include some flavonoids that have pharmacological effects ( Tokunaga et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rat intestine microsomes were prepared as described in our previous report . CYP3A enzyme activity was assessed according to 6β‐OH testosterone formation and which was measured using HPLC previously reported .…”
Section: Methodsmentioning
confidence: 99%
“…Rat intestine proteins were isolated and Western blot analysis was conducted to evaluate CYP3A protein levels according to previous methods . In brief, proteins (12 μg) from total cell lysates were separated using SDS‐PAGE and transferred onto polyvinylidene difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation